Morphogenic processes of adaptability and interconnectedness between urban interventions and informal settlements - Carlos Augusto Martínez Muñoz; Francisco Javier Maroto Ramos (Frontiers of Architectural Research)
Contemporary intervention strategies in Latin America have been mainly based on adaptability and informal interconnection processes based on observing morphogenic evolution in informal settlements. These behaviours were first explored by John F.C. Turner in Peru in the 1960s and Jorge Mario Jáuregui since the 2000s, subsequently used as necessary project tools in planning informal contexts. However, empirical evidence reveals that both processes have been approached individually in the interventions, showing a disconnection in the scale produced and in their complementarity of action. The objective of the study is to identify factors that originate the connection and disconnection of the processes of adaptability and interconnection between the intervention and the informal settlement, establishing a hypothesis that the disconnection produced between both processes reduces the effectiveness of the intervention to the detriment of the informal settlement. As a method, variables involved in these processes are analysed in representative models from the United States, Chile, Brazil, Colombia, and South Africa from a formal (state and private programs) and informal (evolutionary phases) perspective. As a result, the research provides new insights into the insertion of adaptability and interconnectedness processes endowed with greater effectiveness in interventions on informal settlements.